Ownership structure, Sukuk issuance and real earnings management: the moderating effect of shariah compliance and political connections - Aliana Shazma Amir, Amir (2019)
This study examines the relationship between ownership structures, Sukuk issuance and real earnings management by Malaysian public listed companies. It also investigates the moderating roles of Shariah compliance and political connections on the relationship between ownership structures and real earnings management. The study uses 850 firm-year observations drawn from the population of non-financial companies for the period of 2012-2016. Real earnings management is measured using Zang (2012) model. Ownership structures are divided into three types: managerial ownership, external block-holder ownership and family ownership. To achieve the objectives of this study, quantitative method of analysis is employed. The data analysis method used is panel data technique using Feasible Generalized Least Squares (FGLS) to test for the long run relationship. With reference to the agency theory, Maqasid As-Shariah theory, Islamic ethical perspectives and reputational theory, the present study finds that ownership structures are effective mechanisms in mitigating real earnings management while Sukuk issuance are able to provide benchmarks that the managers’ opportunistic behaviour to engage in real earnings management is less prevalence. Besides, the moderating role of Shariah compliance strengthens the effectiveness of ownership structures as monitoring mechanism in mitigating real earnings management. However, the moderating role of political connections weakens the effectiveness of ownership structures in reducing real earnings management. By examining all the determinants of real earnings management, it may assist standard setters, regulators and authorities to stay alert to manifest approaches to attenuate such practices. It is of great significance to assess Malaysian companies since it provides insights into Malaysian corporate environment through examination of companies’ real earnings management practices.